Social Structure, arranged my own marriage’: arranged Marriages and Post-colonial Feminism - Dr. Lahiri-Roy Walker (Al-Qanṭara, 2023)
The study of such changes—their causes, how they occur, and the effects they have—represents a significant area of sociological inquiry. The role of ideational components in family transition is suggested by recent study on the subject (Johnson-Hanks 2011, Thornton 2005). Behavior and its meaning are shaped by ideational elements, sometimes referred to as schemas (Johnson-Hanks 2011) or models of and for reality (Fricke 1997a, Thornton et al. 2001). Schemas are "the mostly underdetermined, and frequently taken-for-granted, methods of perceiving and acting through which we make sense of the world and motivate our behaviours," according to Johnson-Hanks and colleagues (2011:2). Schemas comprise classifications, arbitrary assessments, social norms, and mental images that are both culturally and cognitively based. So, in order to comprehend family transformation. The way families behave has changed significantly in recent decades. One example of this is the drop in planned marriages and parallel rise in "love marriages"—more precisely, self-chosen marriages—across Asia. In the past, arranged marriages—where parents select their children's spouses—were common in many Asian nations. However, in recent years, young people in Nepal (Fricke et al. 1998, Ghimire et al. 2006, Niraula 1994), Indonesia (Malhotra 1991), China (Pimentel 2000), Taiwan (Thornton and Lin 1994), Japan (Applbaum 1995), Korea, and Malaysia have been more active in selecting their own marriages (Rindfuss and Morgan 1983). The study of such changes—their causes, how they occur, and the effects they have—represents a significant area of sociological inquiry. recent studies on family transitions.